Lesser snow goose helminths show recurring and positive parasite infection-diversity relations. Issue 1 (April 2017) - Dargent, Felipe; Morrill, André; Alisauskas, Ray T.; McLaughlin, J. Daniel; Shutler, Dave; Forbes, Mark R.
Abstract: The patterns and mechanisms by which biological diversity is associated with parasite infection risk are important to study because of their potential implications for wildlife population's conservation and management. Almost all research in this area has focused on host species diversity and has neglected parasite diversity, despite evidence that parasites are important drivers of community structure and ecosystem processes. Here, we assessed whether presence or abundance of each of nine helminth species parasitizing lesser snow geese ( Chen caerulescens ) was associated with indices of parasite diversity (i.e. species richness and Shannon's Diversity Index). We found repeated instances of focal parasite presence and abundance having significant positive co-variation with diversity measures of other parasites. These results occurred both within individual samples and for combinations of all samples. Whereas host condition and parasite facilitation could be drivers of the patterns we observed, other host- or parasite-level effects, such as age or sex class of host or taxon of parasite, were discounted as explanatory variables. Our findings of recurring and positive associations between focal parasite abundance and diversity underscore the importance of moving beyond pairwise species interactions and contexts, and of including the oft-neglected parasite species diversity in infection-diversity studies. Graphical abstract: Highlights: We assessed parasite infection-diversity patterns among 9 helminth species from >700 lesser snow geese hosts. 7 helminth species showed recurring positive infection-parasite diversity relations. Those patterns were independent of sex or age category of hosts and not dependent on particular parasite species or taxa. Patterns were robust to different diversity and infection measures. Our study highlights the importance of considering the oft-neglected parasite diversity in infection-diversity studies.